Correction: Micro/nano-net guides M2-pattern macrophage cytoskeleton distribution via Src–ROCK signalling for enhanced angiogenesis. (14th April 2021) - Yang, Yang; Lin, Yujing; Zhang, Zhengchuan; Xu, Ruogu; Yu, Xiaoran; Deng, Feilong
Abstract : Correction for 'Micro/nano-net guides M2-pattern macrophage cytoskeleton distribution via Src–ROCK signalling for enhanced angiogenesis' by Yang Yang et al., Biomater. Sci., 2021, DOI: ; 10.1039/d1bm00116g .